Biomass potential from clear fellings in Latvia - Kons, Kalvis (2011)
In recent years, the importance of renewable energy sources, including biomass, has considerably increased in EU and Nordic regions. The target level for EU is to reach 20% of total energy consumption. Latvia has to increase its share of renewables by 7% to reach its goal of 40% by 2020. The main, and still not fully used, renewable resource is biomass in Latvia. The aim of this study is to evaluate available and potential resources of biomass from clear cuts now and in the future. Core data is taken from the National Forest Inventory (NFI), which is done for the first time in the history of Latvia. Availability of biomass is estimated at three levels and nine sublevels showing the change of available biomass today and in the future if harvest intensity and technologies of collecting energy wood in clear cuts are improved. Also, possible changes in the pulpwood market are reviewed. Level 1 expresses harvest intensity according to data from the State Forest Service. According to data from NFI level 2 shows the same pattern as level 1 and level 3 gives the maximum level of available biomass. Results are expressed in oven dry tones of energy wood. Today the main limiting factor for the expansion of energy extraction from wood from clear cuts is the cost of energy wood. About 20% of all clear cuts are used for energy wood collection. The quantities that are produced today may be increased by about three times by optimizing the utilization of clear cuts used for energy wood extraction and slight improvements in methods and technologies. The main assortment of energy wood at the moment is logging residues and firewood. At level 1, biomass potential is 0.79 m odt (oven dry tons) annually. If, at the same level, stump lifting would be introduced, available biomass would be 0.98 m odt (level 1.1). With improved technologies and optimal land use, biomass for energy would reach 2.54 m odt. If in the market situation price for pulpwood is too low and it is used as energy wood, available biomass would be 3.66 m odt. At the base of level 2, available biomass is 1.06 m odt annually. With the stump lifting at level 2.1, the volume of energy wood is 1.30 m odt. Optimal land use and improved technologies at level 2.2 gives 3.40 m odt. By adding pulpwood biomass potential at the level 2.3, it is possible to reach 4.89 m odt. At the maximum harvest intensity at level 3 biomass potential is 2.21 m odt, level 3.1 gives 2.73 m odt, level 3.2 – 7.10 m odt, and the maximum annually available biomass potential at level 3.3 is 10.23 m odt. It is rather hard to estimate biomass potential from the raw data of NFI, but the results look realistic when compared to other studies. Extra quantities of energy wood could be added from wood processing as a secondary source of biomass, which is not considered in this paper.